Pengembangan Ekstraksi dalam Identifikasi Kelainan Gigi pada Citra Dental X-ray imaging (DXRI) - Sumijan (Jurnal KomtekInfo, 2022)
Dental X-ray imaging (DXRI) has been developed as a basis for dental professionals and professionals around the world to assist in detecting abnormalities in tooth structure. The results of the radiographs assist the imaging assessment to provide a thorough clinical diagnosis and preventive examination of the tooth structure. However, the results of the image analysis from DXRI are not sufficient, it is still necessary to use image processing and analysis methods to extract relevant information. The purpose of this study was to analyze the image of teeth on Dental X-rays by using the image extraction method. The results of this study were able to identify abnormalities in the teeth with a high success rate, namely an average of 83.33% based on testing of 10 dental images. The results of the development of the algorithm have been able to provide optimal results in identifying abnormalities in normal and abnormal teeth. Overall, the results of this study can be used as a medical reference for further medical treatment for dental abnormalities.